2018
DOI: 10.1186/s12877-018-0873-5
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress and frailty in old age: the Helsinki birth cohort study

Abstract: BackgroundEvidence suggests that early life stress (ELS) may extend its effect into adulthood and predispose an individual to adverse health outcomes. We investigated whether wartime parental separation, an indicator of severe ELS, would be associated with frailty in old age.MethodsOf the 972 participants belonging to the present sub-study of the Helsinki Birth Cohort Study, 117 (12.0%) had been evacuated abroad unaccompanied by their parents in childhood during World War II. Frailty was assessed at a mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
4
15
0
1
Order By: Relevance
“…Our results show that MatSep can alter the levels of specific proteostasis markers in adulthood and in advanced age, in a sex-and brain regionspecific manner. These findings are consistent with the notion of ELS negatively influencing later brain health, as has been previously demonstrated in both animal and human studies (Haapanen et al, 2018;Ruiz et al, 2018). Interestingly, most of the MatSep-induced changes in proteostasis marker expression that we observed in adult animals were not seen in aged animals.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that MatSep can alter the levels of specific proteostasis markers in adulthood and in advanced age, in a sex-and brain regionspecific manner. These findings are consistent with the notion of ELS negatively influencing later brain health, as has been previously demonstrated in both animal and human studies (Haapanen et al, 2018;Ruiz et al, 2018). Interestingly, most of the MatSep-induced changes in proteostasis marker expression that we observed in adult animals were not seen in aged animals.…”
Section: Discussionsupporting
confidence: 93%
“…The higher frailty among the adoptees may thus reflect early life stress, caused by being separated from one’s biological family. A similar finding on childhood stress and frailty was recently reported in the Helsinki Birth Cohort Study; those men who were evacuated abroad unaccompanied by their parents in childhood during World War II had a higher risk of frailty (measured using the FP) in late life compared to nonseparated men ( 35 ). However, the Finnish study found no associations in women.…”
Section: Discussionsupporting
confidence: 81%
“…The higher FI among the adoptees may thus reflect early life stress, caused by being separated from one's biological family. A similar finding on childhood stress and frailty was recently reported in the Helsinki Birth Cohort Study; those men who were evacuated abroad unaccompanied by their parents in childhood during World War II had a higher risk of frailty (measured using the FP) in late life compared to non-separated men (29). However, this study found no associations in women.…”
Section: Discussionsupporting
confidence: 88%